Dual-initiating and living frustrated Lewis pairs: expeditious synthesis of biobased thermoplastic elastomers - Yun Bai (Nature Portfolio, 2021)
Biobased poly(γ-methyl-α-methylene-γ-butyrolactone) (PMMBL) has attracted interest because it is biorenewable and exhibits superior properties to petroleum-based linear analog poly(methyl methacrylate) (PMMA). Here the authors report the synthesis of well-defined PMMBL-based ABA tri-block copolymers, enabled by dual-initiating and living frustrated Lewis pairs, which have superior mechanical properties compared to those of PMMA-based tri-BCPs.